ANTIMICROBIAL ACTIVITY OF n-HEXANE EXTRACTS OF RED FRANGIPANI (Plumeria rocea) - Muhammad Ali Husni; Murniana Murniana; Hira Helwati; Nuraini Nuraini (Universitas Syiah Kuala, 2013)
Antimicrobial assay of n-hexane plant extracts against Escherichia coli and Staphylococcus aureus had been done. Extraction with n-Hexane of the flowers yielded 2,08% of extract, while leaves and stems yielded 3,21% and 2,19% of n-hexane extracts, respectively. The extracts showed different activity against both bioindicators. The leaves extracts showed the strongest activity indicated by wider diameters of inhibition zone, 19,7 mm against E. coli and 13,3 mm against S. aureus at 10% of the extracts’ concentration. At the same concentration (10%), the steam and flower extracts showed less inhibitory activities with  11,3 mm and 8,3 mm against E. coli, and 12,0 mm and 11,0 mm against S. aureus. At the lowest concentration of the extracts, the leaves extracts showed the strongest activity against E. coli (14,3 mm) while the steam extracts showed highest inhibitory activity against S. aureus ( 7,7 mm). Based on antimicrobial assay, it was suggested that the leaves extracts demonstrated strongest activity than other extracts. It was assumed that leaves extracts contained more secondary metabolite than flowers and steams, and the leaves have phenol compounds which are not present in other extracts.